(untitled) (Castilla. Estudios de Literatura, 2013)
Abstract: This contribution discusses the exploitation of the narratives of travel within the Letters from Spain (1822) by José María Blanco White. After introducing the author and his biographical circumstances, the Letters will be contextualized within the discursive fields they unite, such as contemporary history, autobiography, essayistic social criticism, and the romantic travel account. In this effect, I focus on the cognitive and ideological forms of perception of the author and the expected readership, the representation of the other, and the interrelations of the travel discourse with other lines of interpreting the altering realities at the beginning of the 19th century.